Development of Bandung City Transport Optimization Application with Best-Path Planning Algorithm on Android Platform: Development of Bandung City Transport Optimization Application with Best-Path Planning Algorithm on Android Platform - Danang Agustian (Institute of Computer Science (IOCS), 2020)
City transport is often used by some people who travel without using their private vehicle. Usually, city transportation is empowered by the city government to encourage people to prioritize public transportation as the main choice for traveling. However, there are several problems such as the difficulty in knowing what city transportation routes can be used to reach a destination in the city, especially the city of Bandung. From the problems that arise, it requires information media that can be a virtual guide in optimizing the use of city transportation. This information media is needed to stimulate the public to always return to using city transportation as the primary means of transportation for travel. Smartphones with the Android operating system are one of the information media that can be used because of the very good development and growth of users in society, this can be seen from a survey conducted on one site, namely StatCounter which shows Android users are getting better in 2014. Therefore The development of this application for optimizing the use of city transportation is expected to be able to provide good information in determining the use of public transportation. On the other hand, the Best - Path Planning method is empowered to support the search for city transportation and decision making for the use of city transportation.